A new strategy of multiplex real-time RT-qPCR assay for differentiating Omicron variants from other SARS-CoV-2 lineages - Chen-Sheng Wu; Bo-Han Chen; Hiu-Lo Cheng; Wei-Ming Huang; Tian-Neng Li; Horng-Dar Wang; Chun-Hsien Kuo (Biotechnology & Biotechnological Equipment)
The global dissemination of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) Omicron variants has been characterized by a distinct 9-base pair (bp) deletion within the nucleocapsid (N) gene, a genomic feature absent in previously circulating variants. In response to this unique characteristic, we have developed an innovative amplicon-competition strategy to differentiate Omicron lineages from other SARS-CoV-2 variants using a real-time reverse-transcriptase polymerase chain reaction (RT-PCR) assay. This novel methodology demonstrates high specificity and sensitivity, effectively detecting viral loads ranging from 1500 to 1.5x106 copies per milliliter in nasopharyngeal swab specimens. The potential applications of this approach extend beyond current needs, providing a robust framework for the genomic characterization of future variants exhibiting unique genetic signatures.